Transport assessment and risk analysis: the case of the 2nd fixed link across the Danube River - Mudova, Nedyalka; Salling, Kim Bang (Proceedings from the Annual Transport Conference at Aalborg University, 2009)
The scope of this paper is to present a new methodology for appraising transport infrastructure projects. Conventionally, transport infrastructure appraisal is conducted by the use of cost-benefit analyses (CBA) in order to produce aggregated single point estimates. However, new research has proved that the embedded uncertainties within traditional CBA such as ex-ante based investment costs and travel time savings are of high significance. This paper investigates the latter two impacts in terms of the Optimism Bias principle which is used to take account of the underestimation of construction costs and the overestimation of travel time savings. By extending this principle into stochastic modelling where a quantitative risk analysis (QRA) is applied, so-called feasibility risk assessment is provided by moving from point (deterministic CBA) to interval (stochastic QRA) results. Hereby, decision support as illustrated in this paper will aim to provide assistance in the development and ultimately the choice of action, while accounting for the uncertainties surrounding transport appraisal schemes. Evidently, the methodological approach is illustrated by a case example from the Northern region of Bulgaria.